Imperatives of foresight and futures thinking in public policy - Perante-Calina, Lizan E. (Philippine Journal of Public Administration, 2022)
This essay stresses the importance of futures thinking as a 21-century skill to craft better public sector policies and decisions. Using the interpretive-historical approach, the article traces initiatives in futures thinking, which is an emerging trend of human intervention in changing mindsets. This essay's contribution is that it indigenizes futures thinking (FT) learning by making use of an old Filipino word, "hiraya," to introduce the phrase "hiraya foresight" as an indigenous, non-western approach to studying, analyzing, and using futures thinking. This new indigenous approach requires that FT learning be reinforced by three companion skills, namely, hiraya foresight, knowledge co-creation, and phronetic leadership.